2014
DOI: 10.1002/ajh.23684
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized trial of high‐dose CEOP + filgrastim versus standard‐dose CEOP in patients with non‐Hodgkin lymphoma: 10‐year follow‐up data: Australasian Leukaemia and Lymphoma Group (ALLG) NHL07 trial

Abstract: on behalf of the ALLG Increasing dose intensity (DI) of chemotherapy for patients with aggressive non-Hodgkin lymphoma (NHL) may improve outcomes at the cost of increased toxicity. This issue was addressed in a randomized trial aiming to double the DI of myelosuppressive drugs. Between 1994 and 1999, 250 patients with previously untreated aggressive NHL were randomized to treatment with six cycles of 3-weekly standard (s) or intensive (i) chemotherapy: s-CEOP-cyclophosphamide 750, epirubicin 75, vincristine 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Peripheral T cell lymphoma (PTCL) is a heterogeneous entity of non-Hodgkin lymphoma (NHL) with aggressive clinical behavior. Although cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) or CHOP-like chemotherapy is widely used in PTCL [1,2], a complete response rate (CRR) ranges from 35.9 to 65.8% and the 5-year overall survival (OS) rate is 38.5% for all PTCL patients receiving front-line anthracyclinebased treatment [3]. Multiple combinational regimens have been attempted in PTCL, including gemcitabine, cisplatin, prednisone (GDP) [4], and ifofamide, epirubicin, and etoposide (IVE) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral T cell lymphoma (PTCL) is a heterogeneous entity of non-Hodgkin lymphoma (NHL) with aggressive clinical behavior. Although cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) or CHOP-like chemotherapy is widely used in PTCL [1,2], a complete response rate (CRR) ranges from 35.9 to 65.8% and the 5-year overall survival (OS) rate is 38.5% for all PTCL patients receiving front-line anthracyclinebased treatment [3]. Multiple combinational regimens have been attempted in PTCL, including gemcitabine, cisplatin, prednisone (GDP) [4], and ifofamide, epirubicin, and etoposide (IVE) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, long-term outcomes remain poor, with a 5year overall survival (OS) rate of only 30% for most PTCL subtypes, 3 except for anaplastic large cell lymphoma (ALCL) with anaplastic lymphoma kinas-positive status. 2,5 Given the poor prognosis of PTCL patients, autologous stem cell transplant (ASCT) as first-line consolidation therapy could be crucial for long-term disease management in eligible patients. However, whether PTCL patients in CR after first-line treatment benefit from ASCT remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The ECHELON‐2 study using brentuximab vedotin plus CHOP has established a new standard of care and demonstrated survival benefits for patients with CD30‐positive PTCL. Nevertheless, long‐term outcomes remain poor, with a 5‐year overall survival (OS) rate of only 30% for most PTCL subtypes, 3 except for anaplastic large cell lymphoma (ALCL) with anaplastic lymphoma kinas‐positive status 2,5 …”
Section: Introductionmentioning
confidence: 99%